Biosynthesis of silver nanoparticles using oak leaf extract and their application for electrochemical sensing of hydrogen peroxide. (3rd September 2018) - Hemmati, Saba; Baghayeri, Mehdi; Kazemi, Sanaz; Veisi, Hojat
Abstract : A green method is proposed for synthesizing silver nanoparticles using oak leaf extract as a reductant, capper and stabilizing agent. The characterization of biosynthesized Ag@oak leaf extract (Ag@OLE) was performed using scanning electron microscopy–energy‐dispersive X‐ray analysis, X‐ray diffraction, transmission electron microscopy and UV–visible spectroscopy. The Ag@OLE nanocomposite was applied for immobilizing haemoglobin (Hb) on the surface of glassy carbon electrode (GCE) and its application as a hydrogen peroxide biosensor of was studied. Electrochemical properties of the biosensor were studied using cyclic voltammetry and electrochemical impedance spectroscopy. Direct electrical communication between the redox centre of Hb and GCE was created via conducting network of Hb–Ag@OLE. Abstract : Biosynthesis of silver nanoparticles using oak leaf extract as a reductant/stabilizing agent, and their application for electrochemical sensing of hydrogen peroxide are described.